Oral ulcer activity assessment with the composite index according to different treatment modalities in Behcet's syndrome: a multicentre study - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2019)
Objective. The aim of this multicentre study was to understand patients' needs and to evaluate the oral ulcer activity with the Composite Index (CI), according to different treatment modalities in Behcet's syndrome (BS). Methods. BS patients (n=834) from 12 centres participated in this cross-sectional study. Oral ulcer activity (active vs. inactive) and the CI (0: inactive vs. 1-10 points: active) were evaluated during the previous month. The effects of treatment protocols [non-immunosuppressive: non-IS vs. immunosuppressive: (ISs)], severity (mild vs. severe), disease duration (<5 years vs. >= 5 years) and smoking pattern (non-smoker vs. current smoker) were analysed for oral ulcer activity. Results. Oral ulcer activity was observed in 65.1% of the group (n=543). In both genders, the activity was higher in mild disease course with non-IS treatment group compared to severe course with ISs (p<0.05). As a resistant group, patients with mild disease course whose mucocutaneous symptoms were unresponsive to non-IS medications were treated with ISs in a limited period and achieved the highest CI scores in females. Oral ulcer activity and poor CI score were associated with disease duration less than 5 years compared to others in male patients (p<0.05). Conclusion. Oral ulcer activity pattern is affected by both the combination of disease course, treatment protocols and disease duration. CI scores reflected the oral clinical activity and CI might be a candidate scale to evaluate the efficacy of treatments during the follow-up of oral ulcer activity in BS.
Keywords: Oral ulcer; Behcet's syndrome; treatment; composite index; gender; OUTCOME MEASURES; DISEASE; MANAGEMENT; MANIFESTATIONS; TESTOSTERONE; INFLAMMATION; ETIOLOGY